PENGARUH STRES KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT. SINAR MITRA SEPADAN FINANCE CABANG PALOPO - Haedar, Haedar; Hadrah, Hadrah (CAM JOURNAL, Jurnal Agen Perubahan Manajemen, 2018)
The objective  of the study was to find out the effect of  work stress and environmental on the performance of employees at PT. Sinar Mitra Sepadan Finance Palopo Branch. The results of study showed that work stress had a positive effect on the performance of employees of PT. Sinar Sepadan Finance Palopo Branch Branch, with a probability value of 0,000 smaller with an alpha of 0.05 (0.000 <0.05). It means that work stress has a  positive and significant effect on employee performance. The results of study  show that the work environment has a positive and significant effect on employee performance. This   \is evidenced by the probability value of 0.007 smaller than alpha 0.05 (0.007 <0.05). Simultaneously, work stress and work environment have a significant effect on employee performance. This is evidenced by the results of multiple linear regression statistical tests obtained by significant value F-count 0,000 alpha 5% value of Sig F <Sig α (0,000 <0,05).